2013
DOI: 10.1115/1.4025065
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach to Estimate the Impact of the Aerodynamic Force Induced by Rotating Stall in a Vaneless Diffuser on the Rotordynamic Behavior of Centrifugal Compressors

Abstract: One of the main challenges of the present industrial research on centrifugal compressors is the need for extending the left margin of the operating range of ihe machines. As a result, interest is being paid to accurately evaluating the amplitude of the pressure fluctuations caused by rotating stall, which usually occurs prior to surge. The related aerodynamic force acting on the rotor can produce subsynchronous vibrations, which can prevent the machine's further operation, in case their amplitude is too high. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
(13 reference statements)
0
10
0
Order By: Relevance
“…The experiments carried out by Abdelhamid (1983) and Bianchini et al (2013) confirmed that the local reverse flow did not necessarily lead to stall. The dependency of flow instability on the diffuser width ratios and diameter were also verified.…”
Section: Introductionmentioning
confidence: 49%
“…The experiments carried out by Abdelhamid (1983) and Bianchini et al (2013) confirmed that the local reverse flow did not necessarily lead to stall. The dependency of flow instability on the diffuser width ratios and diameter were also verified.…”
Section: Introductionmentioning
confidence: 49%
“…The number of stall cells does not change when the radius ratio is 1.5, and the circumferential propagation velocity of stall cells does not develop from low to high. (2). The stall frequency variations in wide vaneless diffusers with different radius ratios are different.…”
Section: Discussionmentioning
confidence: 99%
“…However, instability has plagued the safe and stable operation of small flow compressors, such as rotating stalls and surges. When a rotating stall occurs, the performance of a centrifugal compressor will drop sharply, and the blades will be damaged due to the alternating stress [1][2][3]. Rotating stall can occur in the diffuser and impeller [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5]. As power machinery, a wide, high-efficiency operating range is required for compressors, considering not only the efficiency but also the stability and safety [6][7][8]. However, the behaviors of compressor operating under off-design conditions are subject to various unstable phenomena which could have negative effects on their performance and then lead to further increased losses and energy consumption.…”
Section: Introductionmentioning
confidence: 99%